Cortico-cortical coupling patterns during dual task performance. - Serrien, D; Pogosyan, A; Brown, P (2004)
We investigated the neural correlates of dual task performance using EEG coherence as a measure of the functional coupling between cortical regions. Nine healthy participants performed a rhythmical movement with the right hand and an isometric contraction with the left hand, either initiated simultaneously or successively. EEG data revealed that dual task performance was associated with stronger coherence in left hemispheric and mesial areas than the sum of the tasks performed separately in the beta (>12-30 Hz), but not alpha (8-12 Hz), band. This effect was more pronounced when the two assignments were initiated simultaneously, as opposed to successively. The data demonstrate that the pattern of cortico-cortical coupling during bimanual actions is not just the sum of that associated with its component parts, but is increased according to coordinative demands and processing load.